(untitled) (Al-Academy, 2022)
Theatrical performances began with the Greeks when the theatrical scenes and skeletal figures were encoded, where the large wall of the Alskina, which contains three doors, the middle of them with a high height, and the two sides took the natural size, where the middle door indicated a symbolism of the god or demigods, as we find the condensation of the symbol in the architecture of the theater, and the symbol was taken In the theatrical scene, the development semantically and aesthetically, and interpreting and interpreting the current day, where the laser light formed the symbolism of the contemporary virtual scene, and in order to identify the aesthetics of the symbol in the theatrical scene, the current research was evaluated into four chapters: The first chapter (the methodological framework) which contained the research problem that The question was (What are the aesthetics of the symbol in the Iraqi theatrical appearance?) The aim of the research was (to identify the aesthetics of the symbol in the Iraqi theatrical scene). As for the second chapter (the theoretical framework), it was divided into sections: The first topic: the aesthetic manifestations of the symbol / the second topic: the use of the symbol in the aesthetic theatrical scene. The third chapter came (research procedures), (research community/research sample) (presentation of the picnic play, and research methods (descriptive and analytical), while the fourth chapter contained the research results and conclusions and concluded the research with a list of sources